Prince Caspian : the return to Narnia - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : Collier, 1970)
In this second Chronicle of Narnia, Peter, Edmund, Susan, and Lucy help Prince Caspian organize his army of Talking Beasts to fight against an evil king who has taken control of Narnia.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
5.6
5-8
Keywords: Fantastic fiction; Fantastic fiction